Systems analysis and design in changing world - Satzinger, John W. (Thomson/Course Technology, 2007)
Building on its continued success this text has been revised to provide the most comprehensive, balanced and up-to-date coverage of systems analysis and design available. The Fourth Edition maintains the dual focus on the concepts and techniques from both the traditional, structured approach and the object-oriented approach to systems development. Instructors have the flexibility to emphasize one approach over the other, or both, while referring to one integrated case study that runs through every chapter